Earth-abundant photocatalytic systems for the visible-light-driven reduction of CO2 to CO. Issue 10 (24th February 2017) - Rosas-Hernández, Alonso; Steinlechner, Christoph; Junge, Henrik; Beller, Matthias
Abstract : A highly selective earth-abundant photocalytic system, based on an in situ copper photosensitizer and an iron catalyst, was developed for the CO2 -to-CO transformation. Abstract : Herein, we report a highly selective photocatalytic system, based on an in situ copper photosensitizer and an iron catalyst, for the reduction of CO2 to CO. Turnover numbers (TON) up to 487 (5 h) with selectivities up to 99% and Φ CO = 13.3% were observed. Stern–Volmer analysis allowed us to establish a reductive quenching mechanism between the Cu PS and electron donor.